Au/La2Ti2O7 Nanostructures Sensitized with Black Phosphorus for Plasmon‐Enhanced Photocatalytic Hydrogen Production in Visible and Near‐Infrared Light. Issue 8 (12th January 2017) - Zhu, Mingshan; Cai, Xiaoyan; Fujitsuka, Mamoru; Zhang, Junying; Majima, Tetsuro
Abstract: Efficient utilization of solar energy is a high‐priority target and the search for suitable materials as photocatalysts that not only can harvest the broad wavelength of solar light, from UV to near‐infrared (NIR) region, but also can achieve high and efficient solar‐to‐hydrogen conversion is one of the most challenging missions. Herein, using Au/La2 Ti2 O7 (BP‐Au/LTO) sensitized with black phosphorus (BP), a broadband solar response photocatalyst was designed and used as efficient photocatalyst for H2 production. The optimum H2 production rates of BP‐Au/LTO were about 0.74 and 0.30 mmol g −1  h −1 at wavelengths longer than 420 nm and 780 nm, respectively. The broad absorption of BP and plasmonic Au contribute to the enhanced photocatalytic activity in the visible and NIR light regions. Time‐resolved diffuse reflectance spectroscopy revealed efficient interfacial electron transfer from excited BP and Au to LTO which is in accordance with the observed high photoactivities. Abstract : Solar‐energy conversion : The visible and near‐infrared (NIR) light‐activated photocatalyst Au/La2 Ti2 O7 was sensitized with black phosphorus (BP) and used for photocatalytic H2 production. The broad absorption of BP and plasmonic Au contributed to the improved photocatalytic activity of the catalyst in the visible and NIR light regions.